PENGEMBANGAN SUMBER DAYA MANUSIA: MINAT BERWIRAUSAHA MAHASISWA DENGAN POLA PENDIDIKAN SOFT SKILLS - ANTON AKBAR (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2018)
This paper is motivated by the fact that the interest of students for entrepreneurship is still low. In developed countries at least 2% of the population as entrepreneurs. This paper discusses the method of soft skills education in fostering entrepreneurship interest for students of PTKIN. The purpose of writing this article is to make soft skills as an educational pattern to become an attraction for students of PTKIN to entrepreneurship. The object of this research is PTKIN in Indonesia. While this research method is a case study, that is effort to inculcate entrepreneurship spirit based on soft skills in PTKIN. The result of the research is that the pattern of soft skills education can foster entrepreneurial interest for the students of PTKIN. Furthermore, the recommendation of this research is PTKIN must have high awareness and commitment in developing soft skills, identify the soft skills attribute that has been possessed, establishing soft image brand image, designing concrete steps into academic and non academic agenda, and making blue print of soft skills development to run. In the end if the skills and interests of students to entrepreneurship increases, then graduates of PTKIN will make entrepreneur as his job.